Experimental study on multisolid waste synergistic regeneration fluid backfill materials - Wenjuan Zhou; Can Yang; Niutao Hu (Case Studies in Construction Materials)
This study utilizes soda residue (SR), slag, and phosphogypsum (PG) as components of the cementitious material, with redundant soil (RTS) as the primary raw material. With the target compressive strength of fluid backfill materials ranging from 0.3 to 8.3 MPa, the proportioning is designed by using XRD, SEM, and the trigonometric isoenthalpy diagram design method to study the interaction of multisolid wastes in the cementitious system. The optimal mix proportion is identified as 40–50 % soda residue (SR), 30–50 % slag, and 10–30 % phosphogypsum (PG) for the backfill material. Microstructural analysis reveals that SR and PG provide the necessary SO42- and Cl- for hydration reactions, which react with slag to form C-S-H, AFt, and Friedel's salt (Fs). The interlocking and wrapping interaction among these components enhances the microstructural density of the hydration products, thereby enhancing the compressive strength macroscopically. This study integrates multisolid wastes into a sustainable engineering solution, contributing to the circular economy and waste valorization in the construction industry.